2021
DOI: 10.21203/rs.3.rs-200129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-Internexin expression in photoreceptor-like cells of the developing chicken pineal gland

Abstract: BackgroundIt has been reported that some pinealocytes have similar functions to retina photoreceptors in many non-mammalian vertebrates. Two types of pinealocytes, rudimentary-receptor pinealocytes and secretory pinealocytes, have been identified in the pineal gland of juvenile gull, but whether they exist in the chicken pineal gland was unknown. Hence, the purpose of this study was to investigate chicken α-internexin (chkINA) expression patterns in photoreceptor-like cells of the developing chicken pineal gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…According to [ 49 ], the pineal gland is populated by three main cell types: photoreceptor-like cells, pinealocytes, and supporting cells. The latter mainly consist of ependymal and astrocyte-like cells.…”
Section: Evolution Of the Pineal Gland And How Light Influences Secre...mentioning
confidence: 99%
See 3 more Smart Citations
“…According to [ 49 ], the pineal gland is populated by three main cell types: photoreceptor-like cells, pinealocytes, and supporting cells. The latter mainly consist of ependymal and astrocyte-like cells.…”
Section: Evolution Of the Pineal Gland And How Light Influences Secre...mentioning
confidence: 99%
“…Another study showed that visinin in chick pinealocytes increased significantly after continuous light exposure, indicating the photosensitivity of pinealocytes and a possible role of visinin in photoreception [ 49 , 59 ]. Visinin is the specific marker of cone photoreceptor cells in the chicken retina [ 49 , 74 , 75 ]. Hao et al [ 49 ] used visinin to identify photoreceptor-like cells in the chicken pineal gland.…”
Section: Evolution Of the Pineal Gland And How Light Influences Secre...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since it functions like a primitive eye responsible for the perception of light, it is also called the parietal eye, primitive eye, third eye or apical eye (Altınbay, 2020; Kumar & Meshram, 2020; Tainika & Bayraktar, 2022). Birds have a very different pineal gland structure morphologically and cytologically (Hao et al., 2021; Petrusewicz‐Kosinska et al., 2019; Prusik, 2022; Ralph, 2020; Sapède & Cau, 2013). The structure of the organ shows significant changes during the incubation periods (Calvo & Boya, 1978, 1979; Jov'e et al., 1999; Möller & Möller, 1990; Ohshima & Matsuo, 1988).…”
Section: Introductionmentioning
confidence: 99%